Draft of robotic workstation for laser engraving - Klimenda, Frantisek; Sterba, Jan; Cernohlavek, Vit; Ponikelsky, Josef; Maran, Petr (Manufacturing Technology Journal, 2021)
The article deals with the design of a robotic workplace for laser engraving. The first part of the article describes the importance of introducing robotics to industry 4.0. Custom solutions work is devoted to the implementation of the six-axis robotic arm UR10. This six-axis robotic arm inserts the designed jig with the semi-finished product into the engraving machine. In the engraving machine, the semi-finished product is engraved on the final product. This saves the operator time to pinpoint the position of the semi-finished product inside the engraving machine. The proposed jig is designed to be universal so that the position in the x-axis and in the y-axis can be precisely defined. At the end of the jig there is a bed for placing the semi-finished product, which can be replaced by another in the case of other dimen-sions of the semi-finished product. The conclusion is a comparison of time savings in individual steps and overall engraving time savings for one engraved part.
Keywords: Robotic Arm; Laser; Engraving; Marking